2011
DOI: 10.4330/wjc.v3.i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Manual aspiration thrombectomy in acute ST elevation myocardial infarction: New gold standard

Abstract: Percutaneous coronary intervention (PCI) is the preferred method to treat ST segment myocardial infarction (STEMI). The use of thrombus aspiration (TA) may be particularly helpful as part of the PCI process, insofar as the presence of thrombus is essentially a universal component of the STEMI process. This article reviews evidence favoring the routine use of TA, and the limitations of these data. Based on current evidence, we consider TA to be an important maneuver during STEMI PCI, even in the absence of visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…10 One-year mortality, however, was not a pre-specified endpoint in TAPAS and mortality rates in this trial were higher compared with other recent PPCI studies. 20 The late mortality benefit seen in TAPAS may be explained by the possible beneficial effect of thrombectomy on LV remodelling and infarct size. 21 Five subsequent meta-analyses of mortality outcomes with thrombus aspiration during PPCI have been published; two demonstrating a reduction in mortality with thrombectomy 11,22 and the other three reporting neutral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…10 One-year mortality, however, was not a pre-specified endpoint in TAPAS and mortality rates in this trial were higher compared with other recent PPCI studies. 20 The late mortality benefit seen in TAPAS may be explained by the possible beneficial effect of thrombectomy on LV remodelling and infarct size. 21 Five subsequent meta-analyses of mortality outcomes with thrombus aspiration during PPCI have been published; two demonstrating a reduction in mortality with thrombectomy 11,22 and the other three reporting neutral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…But in almost every case thrombus aspiration is followed by coronary stent implantation on atherosclerotic basis. [ 6 ] For better coronary reperfusion, IABP support also was considered the first option to improve coronary insufficiency and prevent heart function failure in the course of cardiogenic shock. Flugelman et al [ 7 ] reported the first surviving patient who was treated with only an IABP following LMCA occlusion.…”
Section: Discussionmentioning
confidence: 99%